Mobile-mediated home-school partnership: attitudes and expectations of teachers, parents and students - Castelli, Stefano; Pieri, Michelle (International Journal about Parents in Education, 2023)
In the past decades, mobile communication has been one of the fastest growing businesses in the world. In Italy, like in others European countries, there are more mobile phones than inhabitants. Everyone is able to use a mobile phone (contrary to a computer, the simple training necessary to use a cell-phone is done quickly and informally). Mobile communication has become an important part of our everyday life.  In schools, mobile phones are generally considered to be a nuisance; but given their pervasive diffusion, they could also be used as a means to foster parent-teacher communication.  In our paper, the results of three focus groups are presented, showing different and sometimes conflicting expectations and attitudes of teachers, parents and students toward a mobile-mediated home-school partnership.